A Dendrimer-Based Dual Radiodense Element-Containing Nanoplatform for Targeted Enhanced Tumor Computed Tomography Imaging - Xiao, Tingting (Langmuir : the ACS journal of surfaces and colloids, 2020)
The exploration of original computed tomography (CT) imaging contrast agents with enhanced sensitivity and specificity is currently one of the major challenging tasks for precision medicine. Herein, we develop an innovative nanoprobe of dendrimer-stabilized gold nanoparticles (Au DSNs) linked with folic acid (FA) as a targeting ligand and diatrizoic acid (DTA) for specific enhanced tumor CT imaging. In current work, poly(amidoamine) (PAMAM) dendrimers of generation 5 (G5) with amine termini were adopted to entrap Au NPs through a stepwise complexation/reduction method to achieve a higher Au loading than the conventional one-step complexation/reduction method. The prepared [(Au0)120-G5.NH2] NPs were sequentially functionalized with diatrizoic acid (DTA), a typical CT contrast agent based on iodine(I), FA through a poly(ethylene glycol) (PEG) spacer, and carboxylated PEG monomethyl ether (mPEG-COOH), ended with complete acetylation of the leftover dendrimer amine termini. The generated Au DSNs-DTA-FA (Au core diameter = 5.9 nm) were thoroughly characterized. Our data reveal that the Au DSNs-DTA-FA containing Au and I dual radiodense elements are stable, display enhanced CT imaging performance, much higher than the single-radiodense elemental material solely based on Au or I, and possess a quite good cytocompatibility. With the demonstrated FA-rendered specific targeting, the developed Au DSNs-DTA-FA can be employed as a highly efficient nanoprobe for targeted enhanced CT imaging of cancer cells and a subcutaneous tumor model. Overall, the created Au DSNs-DTA-FA may be a powerful nanoprobe for specific enhanced CT imaging of various kinds of FA receptor-expressing tumors or biosystems